Screening for novel compounds produced by Actinobacteria and Gardnerella vaginalis that impact HIV-1 infection - Cohen, Arad (Division of Medical Biochemistry, 2023)
HIV-1 infection continues to impact the lives of millions, with the most vulnerable being women living in Sub-Saharan Africa. Variation in the outcome of antiretroviral (ARV) and preexposure prophylaxis (PrEP) clinical trials is most likely multifactorial which could include Bacterial Vaginosis (BV), a condition associated with increased HIV acquisition and decreased tenofovir (TVF) efficacy. It is therefore important to not only understand how BV impacts HIV infection but also to identify alternative, novel ARVs. Natural products (NPs) have been harnessed and used as antibiotics, antifungals, and anti-virals and may represent a source of novel HIV drugs. This study determined whether NPs produced by selected filamentous actinobacteria and the BV-associated bacterium (BVAB) Gardnerella vaginalis (GV) could impact HIV infection. NPs from 23 actinobacteria strains were extracted and tested on pseudovirus (PSV) infection. Ten strains showed a range of anti-viral activity from 50 µg/mL to 25 µg/mL, and the identity of the NPs was determined through mass spectrometry and the Global Natural Products Social Molecular Networking (GNPS) database. These strains produced known antimicrobials: Actinomycin D, Valinomycin, Antimycin, Puromycin and Anisomycin. As some commercial antibiotics have been shown to have antiviral activity, we tested the ability of the antimicrobials to inhibit PSV infection. However, we were unable to determine accurate IC50 values due to the cytotoxicity of all the compounds. Further analysis is required to identify antimicrobial concentrations that are not cytotoxic but are still able to inhibit PSV infection. Surprisingly, preliminary data indicated that GV, the most common bacterial species associated with BV, inhibited HIV infection (Unterpertinger and Abrahams, unpublished data). When PSV infection was measured in the presence of GV supernatant, PSV infection was significantly inhibited, suggesting that either the bacteria released a compound that impacted HIV infection or the culture medium, BHI was reducing infection. Ammonium sulphate (AS) precipitation was performed to isolate compounds from the supernatant of GV but, none of the fractions showed significant anti-viral activity. Subsequently, to confirm whether GV produced organic compounds that may be inhibitory, NPs were extracted from the abiotic culture medium using liquid-liquid extraction (LLE) and solid-phase extraction (SPE). A midpolar fraction was identified that displayed anti-viral properties without reducing cell viability. After the fraction was analyzed by mass spectrometry and screening of the GNPS database, Vitamin B6 was identified as the possible inhibitor. Therefore, this study has identified compounds produced by filamentous actinobacteria and GV that might be novel inhibitors of HIV infection and further study is required to confirm their efficacy.